1992
DOI: 10.1128/iai.60.8.3396-3404.1992
|View full text |Cite
|
Sign up to set email alerts
|

Adoptively transferred anti-idiotype pulsed B cells mediate autoimmune myocarditis

Abstract: Syngeneic mice receiving adoptively transferred enriched B cells or splenocytes pulsed in vitro with polyclonal anti-idiotypic antibodies (anti-Ids) against anti-CVB3 virus antibodies developed coxsackievirus B3 antigenbinding and virus-neutralizing antibodies during a 30-day period, in addition to overt expression of autoimmune myocarditis. Adoptive transfer of anti-Id pulsed T cells resulted in delayed appearance and transient expression of antiviral antibodies, and antiviral antibodies were marginal to abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Passive transfer of anticardiac myosin antibodies from MCMV‐infected mice induced inflammation and necrosis of the myocardium in uninfected recipient mice 41 . Similarly, adoptive transfer of B cells or splenocytes pulsed in vitro with anti‐idiotypic antibodies against anti‐CB3 antibodies induced both antibody production and myocarditis in recipient mice 42 . Efficacious IFNB treatment was associated with reduced B‐cell infiltration in the myocardium during the chronic phase.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Passive transfer of anticardiac myosin antibodies from MCMV‐infected mice induced inflammation and necrosis of the myocardium in uninfected recipient mice 41 . Similarly, adoptive transfer of B cells or splenocytes pulsed in vitro with anti‐idiotypic antibodies against anti‐CB3 antibodies induced both antibody production and myocarditis in recipient mice 42 . Efficacious IFNB treatment was associated with reduced B‐cell infiltration in the myocardium during the chronic phase.…”
Section: Discussionmentioning
confidence: 94%
“…Autoantibodies binding to cardiac myosin, which cross‐react with viral antigenic determinants, are implicated in the development of chronic disease 8 , 41 . Previous studies have demonstrated that B cells mediate autoimmune myocarditis 42 . Passive transfer of anticardiac myosin antibodies from MCMV‐infected mice induced inflammation and necrosis of the myocardium in uninfected recipient mice 41 .…”
Section: Discussionmentioning
confidence: 98%